DAMPAK RETRET ROHANI DAN MATA KULIAH SPIRITUALITAS KATEKIS TERHADAP PEMBENTUKAN KARAKTER MAHASISWA CALON GURU AGAMA KATOLIK - Tinenti, Hemma Gregorius (Lembaga Penelitian STKIP Widya Yuwana, 2023)
Character as a messenger is an important factor that must be present in students who are prospective Catholic religion teachers or catechists. In fact, coaching for students to have character is still very minimal. This research was conducted to obtain information regarding character building which is carried out through spiritual retreats and Catechical Spirituality courses. This study involved students as research subjects. The data collection process was carried out through observation, questionnaires, discussions, and interviews with students and heads of study programs. This research provides information that through spiritual retreats, students are fostered to be able to live the character of Christ; can build a relationship with God and others. Respondents felt that spiritual retreat activities were also very useful, namely at 83.1%. But not in Catechist Spirituality lectures. According to the students, lectures are only theoretical and have no impact on increasing student awareness to live the character of Christ as a role model. Following up on the findings of this research, it is hoped that the study program will choose lecturers who are appropriate and competent and have experience as catechists not only in prohibiting theory but also being able to share their experience in creating.